Cosmogenic 36Cl exposure ages reveal a 9.3 ka BP glacier advance and the Late Weichselian-Early Holocene glacial history of the Drangajökull region, northwest Iceland. (15th October 2015) - Brynjólfsson, Skafti; Schomacker, Anders; Ingólfsson, Ólafur; Keiding, Jakob K.
Abstract: We present twenty-four new cosmogenic isotope ( 36 Cl) surface exposure ages from erratic boulders, moraine boulders and glacially eroded bedrock that constrain the late Weichselian to Holocene glacial history of the Drangajökull region, northwest Iceland. The results suggest a topographically controlled ice sheet over the Vestfirðir (Westfjords) peninsula during the last glaciation. Cold based non-erosive sectors of the ice sheet covered most of the mountains while fjords and valleys were occupied with erosive, warm-based ice. Old 36 Cl exposure ages from highlands and mountain plateaux (L8; 76.5 ka and H1; 41.6 ka) in combination with younger erratic boulders (L7; 26.2 and K1–K4; 15.0–13.8 ka) superimposed on such surfaces suggest the presence of non-erosive ice over uplands and plateaux in the Vestfirðir peninsula during the last glaciation. Glacially scoured terrain and erratic boulders yielding younger exposure ages (L1-L6; 11.3–9.1 ka and R1, R6-R7; 10.6–9.4 ka) in the lowland areas indicate that the valleys and fjords of the Vestfirðir peninsula were occupied by warm-based, dynamic ice during the last glaciation. The deglaciation of mountain Leirufjall by 26.2 ka BP suggests that ice thinning and deglaciation of some mountains and plateaux preceded any significant lateral retreat of the ice sheet. Subsequently this initial ice thinning was followed by break-up of the shelf based ice sheet off Vestfirðir about 15 ka BP. Hence, the new exposure ages suggest a stepwise asynchronous deglaciation on land, following the shelf break-up with some valleys and most of the highlands, ice free by 14–15 ka BP. The outermost moraine at the mouth of Leirufjörður is dated to 9.3 ka BP, and we suggest the moraine to be formed by a glacier re-advance in response to a cooler climate forced by the reduced Atlantic Meridional Overturning Circulation at around 9.3 ka BP. A system of moraines proximal to the 9.3 ka moraine in Leirufjörður as well as a 9.4 ka deglaciation age in the coastal area of Reykjarfjörður suggest that an extensive ice cap persisted over the eastern Vestfirðir peninsula at least until c. 9 ka BP. Highlights: 24 new 36 Cl exposure ages constrain the glacial history of northwest Iceland. A topographically confined ice cap covered northwest Iceland during LGM. Warm-based erosive ice occupied valleys, while cold-based ice covered uplands. Glaciers advanced 9.3 ka BP as a response to melt-water forced climate cooling. Glaciation persisted longer around Drangajökull in NW Iceland than elsewhere in Iceland.